2022
DOI: 10.3390/rs14071589
|View full text |Cite
|
Sign up to set email alerts
|

Aloft Transport of Haze Aerosols to Xuzhou, Eastern China: Optical Properties, Sources, Type, and Components

Abstract: Rapid industrialization and urbanization have caused frequent haze pollution episodes during winter in eastern China. Considering that the vertical profile of the aerosol properties changes significantly with altitude, investigating aerosol aloft information via satellite remote sensing is essential for studying regional transport, climate radiative effects, and air quality. Through a synergic approach between lidar, the AErosol RObotic NETwork sunphotometer observations, and WRF-Chem simulations, several tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 68 publications
1
4
0
Order By: Relevance
“…Ref. [16] uncovered that the maximum of σ, VDR, AOD 500 , AE 440-870nm and FMF in Xuzhou were 1.0 km −1 , 0.10 ± 0.01, 0.68 ± 0.26, 1.30 ± 0.12 and 0.81 ± 0.09, respectively, during heavy haze event, which were comparable to the results of this study. From Figure 11, we could see that the mass concentrations of surface six air pollutants and ratio of PM 2.5 /PM 10 increased strikingly from 30 December 2020 to 2 January 2021, and reached a highest value at 13:00 on 2 January, then suddenly decrease since 14:00 on 2 January, which was coincident with the aerosol vertical profiles and variations of spectral AOD behaviors.…”
Section: Aerosol Vertical Profiles and Optical Properties Affected By...supporting
confidence: 89%
See 2 more Smart Citations
“…Ref. [16] uncovered that the maximum of σ, VDR, AOD 500 , AE 440-870nm and FMF in Xuzhou were 1.0 km −1 , 0.10 ± 0.01, 0.68 ± 0.26, 1.30 ± 0.12 and 0.81 ± 0.09, respectively, during heavy haze event, which were comparable to the results of this study. From Figure 11, we could see that the mass concentrations of surface six air pollutants and ratio of PM 2.5 /PM 10 increased strikingly from 30 December 2020 to 2 January 2021, and reached a highest value at 13:00 on 2 January, then suddenly decrease since 14:00 on 2 January, which was coincident with the aerosol vertical profiles and variations of spectral AOD behaviors.…”
Section: Aerosol Vertical Profiles and Optical Properties Affected By...supporting
confidence: 89%
“…And the maximum σ changed from 0.50 km −1 on 31 December 2020 to 0.60 km −1 on 1 January and 0.68 km −1 on 2 January 2021, whereas the VDR value remained stably at 0.03~0.12 throughout the haze pollution process. This directly demonstrated that the fine-mode and spherical aerosol particles were predominant during the heavy haze period [14,16]. Diverse gaseous precursors emitted by human activities were firmly trapped in PBL under calm and stable thermal inversion layer and hard to spread out, which readily generated different types of aerosol particles through various complex liquid phase chemical reactions or photochemical reactions.…”
Section: A Serious Haze Episode Identified By Ground-based Ozone Lidarmentioning
confidence: 86%
See 1 more Smart Citation
“…This model can be used to maximize the coverage of demand points when the number of facilities is limited. The collective coverage model and the maximum coverage model consider various factors that influence the layout of fire stations and incorporate constraint conditions [32]. To maximize the coverage of fire stations, Equations ( 4)-( 7) are applied:…”
Section: Maximum Coverage Modelmentioning
confidence: 99%
“…Shifting the focus to another major atmospheric issue, dust, primarily from the Sahara, poses a distinct challenge in aerosol monitoring. It significantly impacts air quality, sunlight exposure, and ecosystems [7,13,14]. Sentinel-3, equipped with the Ocean and Land Color Instrument (OLCI) and the Sea and Land Surface Temperature Radiometer (SLSTR), provides important information for identifying and monitoring dust events.…”
Section: Introductionmentioning
confidence: 99%